Reversible Suppression of Fear Memory Recall by Transient Circadian Arrhythmia - Steiger, Athreya; Farfan, Julia; Fisher, Nathan; Heller, H. Craig; Fernandez, Fabian-Xosé; Ruby, Norman F. (Frontiers in Integrative Neuroscience, 2022)
We tested the hypothesis that a temporary period of circadian arrhythmia would transiently impair recall of an aversive memory in Siberian hamsters (Phodopus sungorus). Hamsters were conditioned to associate footshocks with a shock chamber (context) and with a predictive auditory tone (cue), and then exposed to the disruptive phase-shift (DPS) protocol. Following DPS, animals either became circadian-arrhythmic (ARR), reentrained to the light-dark cycle (ENT), or became arrhythmic for <14 days before their circadian locomotor rhythms spontaneously recovered and reentrained (ARR-ENT). When tested for contextual memory during the period when both ARR and ARR-ENT groups were arrhythmic (day 9 post-DPS), freezing was significantly decreased. Once ARR-ENT animals reentrained, however, freezing increased to Pre-DPS levels (day 41 post-DPS). ENT animals maintained high levels of freezing at both time points, whereas, freezing remained low in ARR hamsters. In contrast to contextual responses, cued responses were unaffected by circadian arrhythmia; all three groups exhibited elevated levels of freezing in response to the tones. The differential impact of circadian arrhythmia on contextual versus cued associative memory suggests that arrhythmia preferentially impacts memory processes that depend on the hippocampus.